2020
DOI: 10.1007/s00107-020-01554-5
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of different wood-based materials against mould fungi: a comparison of methods

Abstract: Wood-based materials are generally prone to colonization by mould fungi and other discoloring microorganisms, but their resistance to fungal discoloration varies. Different standardized test methods for determining the susceptibility to mould fungi have been used to evaluate various wood-based materials, but the obtained results suggest that mould resistance depends on the method applied. Therefore, this study aimed at a comparative evaluation of two commonly used methods for determining the mould resistance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…It means that tung tree oil fills the pores and voids in the obtained biocomposite, as well as the valves, vessels, and tracheids in HS, consequently reducing the possibility for fungal hyphae to penetrate. Although, as Figure 3 and Figure 5 d–f show, it still occurs after 6 months of incubation with microorganisms because the time for fungus growth test plays an important role because fungus infestation risk increases with incubation time [ 43 , 44 ] as the weight loss of the samples increases. It can also be noted that the composition of biocomposite impregnated with tung tree oil includes expandable graphite as a flame retardant, which is a carbon-based material that reduces susceptibility to microbial degradation of composite materials [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…It means that tung tree oil fills the pores and voids in the obtained biocomposite, as well as the valves, vessels, and tracheids in HS, consequently reducing the possibility for fungal hyphae to penetrate. Although, as Figure 3 and Figure 5 d–f show, it still occurs after 6 months of incubation with microorganisms because the time for fungus growth test plays an important role because fungus infestation risk increases with incubation time [ 43 , 44 ] as the weight loss of the samples increases. It can also be noted that the composition of biocomposite impregnated with tung tree oil includes expandable graphite as a flame retardant, which is a carbon-based material that reduces susceptibility to microbial degradation of composite materials [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation weakens the interaction between liquid water and wood as seen with lowfield NMR spectroscopy [49,50] and from the decrease in contact angle with water [7][8][9][10]. For this reason, acetylation is expected to decrease the rate of liquid water uptake by capillary suction which has also been observed for acetylated alder [51].…”
Section: Hygroscopicity and Liquid Water Absorptionmentioning
confidence: 97%
“…In damp environments, the surface of wood may also be colonized by mold fungi. While mold fungi do not affect the strength of wood [9], and molds may grow on many surfaces in addition to wood, molds discolor wood and may present a health hazard in the indoor environment [10]. Finally, at high moisture contents, metal fasteners embedded in wood are subject to corrosion from organic acids and other chemicals [11].…”
Section: Introduction: Wood As a Renewable Building Materialsmentioning
confidence: 99%
“…It was found that softwoods generally contained higher amounts of antifungal extractives, which resulted in higher resistance comparing to hardwoods. It has also been hypothesized that the larger content of hemicelluloses contributes to the higher mould resistance of softwoods over hardwoods [19]. On the other hand, the mould resistance of heat-treated wood is only slightly improved, despite the significantly reduced amount of hemicelluloses [20,21].…”
Section: Introductionmentioning
confidence: 99%